Selected Topics in Myasthenia Gravis - Jaber Al-Zwaini, Isam; AL-Mayahi, Ali (IntechOpen, 2019)
Myasthenia gravis is a rare potentially fatal chronic autoimmune disorder. Circulating autoantibodies directed against components of the neuromuscular junction of skeletal muscles, most commonly nicotinic acetylcholine receptor and associated protein in the postsynaptic membrane, block neuromuscular transmission resulting in muscle weakness. This muscle weakness typically worsens with continued activity, improves on rest, and is of variable severity ranging from mild ocular muscle weakness to severe generalized muscle weakness, involving the respiratory muscle with impending respiratory failure. The worldwide prevalence of myasthenia gravis is 100-200 per million population, affecting more than 700,000 people all over the world. The prevalence rate has increased since the 1950s due to improved diagnostic precision and decreased mortality rate.